2019
DOI: 10.3389/fpsyt.2019.00777
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Healthy Older Adults With a History of Childhood Adversity—Findings From the Women 40+ Healthy Aging Study

Abstract: Background: Adversity in early development seems to increase the risk of stress-related somatic disorders later in life. Physiologically, functioning of the hypothalamic–pituitary–adrenal and hypothalamic–pituitary–gonadal axes is often discussed as long-term mediators of risk. In particular, DNA methylation in the glucocorticoid receptor gene promoter (NR3C1) has been associated with type and strength of early life adversity and subsequent effects on HPA axis signaling in humans. Animal studies, moreover, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 78 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…However, this change seemed independent of the cortisol response to stress in those unexposed and mildly or moderately ELS-exposed individuals ( Alexander et al, 2018 ). What is more, one study that enrolled healthy women aged 40 + assumed no significant associations between childhood adversity and DNAm in the NR3C1 promoter but higher DNAm in the ERα shore correlated with higher levels of adversity ( Fiacco et al, 2019 ). In addition, childhood maltreatments and MDD induced different epigenetic changes at the NR3C1 promoter.…”
Section: Epigenetic Studies Focused On Human Beingsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this change seemed independent of the cortisol response to stress in those unexposed and mildly or moderately ELS-exposed individuals ( Alexander et al, 2018 ). What is more, one study that enrolled healthy women aged 40 + assumed no significant associations between childhood adversity and DNAm in the NR3C1 promoter but higher DNAm in the ERα shore correlated with higher levels of adversity ( Fiacco et al, 2019 ). In addition, childhood maltreatments and MDD induced different epigenetic changes at the NR3C1 promoter.…”
Section: Epigenetic Studies Focused On Human Beingsmentioning
confidence: 99%
“…It was only childhood maltreatments, rather than the depressive symptoms, that were associated with reduced NR3C1 expression ( Bustamante et al, 2016 ). Therefore, though most studies supported that ELS increased the NR3C1 DNAm and possibly that the epigenetic alterations resulted in a blunt HPA axis, emerging evidence indicated that even ELS altered NR3C1 DNAm, this molecular change may not be powerful enough to develop depression ( Tyrka et al, 2016 ; Alexander et al, 2018 ; Fiacco et al, 2019 ). It was reported that depressive patients harbored different profiles of the HPA axis, which might be due to a feature of the NR3C1 DNAm ( Malhi and Mann, 2018 ).…”
Section: Epigenetic Studies Focused On Human Beingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women aged 40-75 years were recruited in the context of the Women 40+ Healthy Aging Study, a larger cross-sectional investigation including healthy middle-aged and older women [72][73][74]. To be included in the study, women had to report good, very good, or excellent health.…”
Section: Subjectsmentioning
confidence: 99%
“…For epigenetic analyses, we perform a bisulfite conversion of DNA using the EZ 96-DNA Methylation-Gold Kit (Zymo Research, Luzern, Switzerland). The procedure for the next-generation sequencing (NGS) library preparation is described elsewhere by our research group [80].…”
Section: Biochemical Data Analysesmentioning
confidence: 99%